Auto-Fluorescence in Phytoliths—A Mechanistic Understanding Derived From Microscopic and Spectroscopic Analyses - Puppe, Daniel; Leue, Martin; Sommer, Michael; Schaller, Jörg; Kaczorek, Danuta (Frontiers in Environmental Science, 2022)
The detection of auto-fluorescence in phytogenic, hydrated amorphous silica depositions (phytoliths) has been found a promising approach to verify if phytoliths were burnt or not in archaeological contexts. However, it is unknown so far at which temperatures auto-fluorescence is induced in phytoliths. We used fluorescence microscopy, scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDX), and Fourier transform infrared (FTIR) spectroscopy to analyze auto-fluorescence in modern phytoliths extracted from plant samples or in intact leaves of winter wheat. Leaves and extracted phytoliths were heated at different temperatures up to 600°C. The aims of our experiments were (i) to find out which temperature is needed to induce auto-fluorescence in phytoliths and (ii) to detect temperature-dependent changes in the molecular structure of phytoliths related to auto-fluorescence. We found organic compounds associated with phytoliths to cause auto-fluorescence in phytoliths treated at temperatures below approx. 400°C. In phytoliths treated at higher temperatures, i.e., 450 and 600°C, phytolith auto-fluorescence was mainly caused by molecular changes of phytolith silica. SEM-EDX analyses revealed that extractable phytoliths were dominated by lumen phytoliths (62%) compared to cell wall phytoliths (38%). Our findings might be not only relevant in archaeological phytolith-based examinations, but also for studies on the temperature-dependent release of silicon from phytoliths as well as the potential of long-term carbon sequestration in phytoliths.